Pendekatan Metode Prototype Pada Aplikasi Presensi Berbasis Mobile (Studi Kasus: Kantor Desa Mekar Jaya) - Eri Bayu Pratama; Ade Hendini; Angga Fristian (LPPM Universitas Bina Sarana Informatika, 2023)
The village office as a government agency at the lowest level requires an information system that can help manage employee attendance data more efficiently. This research aims to design a mobile-based attendance application for the village office using the prototype method. The prototype method was chosen to facilitate the application design, so that the application can be immediately used by village office employees. This research was conducted by collecting data through interviews and observations at the village office that became the subject of the study. The data was then used as a basis for designing the attendance application using the prototype method. The result of this research is a mobile-based attendance application that can be used by the village office to manage employee attendance data more efficiently. This application can also help improve the accuracy of employee attendance data and reduce the risk of errors in the data management process. In conclusion, the use of the prototype method can help accelerate the process of developing attendance applications at the village office and improve the effectiveness of managing employee attendance data.